Stereotip etnis dalam masyarakat multietnis - Warnaen, Suwarsih (Jogjakarta : Matabangsa, 2002)
Ethnic stereotype attitude and the perception of cross-cultural differences among the ethnic groups in Indonesia
Daftar pustaka : p. 407-46
Keywords: Racism in psychology; Racism in psychology -- Indonesia; Ethnic attitudes -- Indonesia; Race awareness; Indonesia -- Ethnic relations